Assessment of anxiety - Mcmanus, F (2004)
Assessment has a number of purposes. • Primarily it aims to identify the nature and severity of the patient's anxiety and to reach a valid diagnosis. • It elicits information for case conceptualization and treatment, and to establish baselines against which change can be measured. • It may be used to determine specific goals for treatment and to begin to socialize the patient into the model of treatment. • It should also consider the main focus of the patient's fears, as it is clear that particular beliefs (cognitions) are crucial in the psychological understanding and treatment of anxiety. © 2004 Elsevier Ltd. All rights reserved.